The teeny tiny woman - O'Connor, Jane (U.S.A : Random House, 1986)
A teeny tiny woman who puts a teeny tiny bone she find in a churchyard away in a cupboard before she goes to sleep is awakened by a voice demanding the return of the bone.
Keywords: Ghost -- Folklore; Folklore -- England